Risks Quantification - Jan Mikolaj (Communications - Scientific letters of the University of Zilina, 2002)
Risk is an inherent phenomenon of every human activity, of every social existence, of every human being. Risk is not coming into existence accidentally but is a part of incertitude and uncertainty that each entity is coupled with. Everybody shall judge what kind of influence has an occurring risk on his own action and what is its significance in a given while. In fact, human being lives in certain social and natural environment which also contains danger fragments. Therefore, it advisable to determine some rules how to evaluate possible risk situations. In this article some of possible solutions are interpreted.